PENGARUH PEMBELAJARAN BERBASIS DARING TERHADAP PRESTASI MAHASISWA PRODI DIPLOMA III KEBIDANAN - Norma Jeepi Margiyanti; Trisna Yuni Handayani*; Nelli Roza (Jurnal Visi Ilmu Pendidikan, 2022)
Pandemic situation covid-19 that hit the world, made everyone forced to isolate themselves in the house, causing all activities to be done at home, including the teaching and learning process. Home learning activities are still carried out using online methods.The purpose of this study is to find out the influence of online-based learning on student learning achievement. The samples in this study were all students of Diploma Three Midwifery Program numbering 70 people.This research uses descriptive design with quantitative approach, data analysis used chi square. The results of the study have the effect of online-based learning on student achievement. Obtained a significance score of 0.025 smaller than 0.05 which means that online learning has an influence on student achievement (P<0.05). It is expected that parents can supervise during the implementation of learning, and it is expected that lecturers can use the right methods so that the material can be absorbed by students properly.